(untitled) (Innovative professional education, 2025)
The article justifies the relevance of the application and characterizes the essence of cyber-hunting as a type of internet project and a manifestation of gamification in the educational process. It explores the potential for implementing this technology in the professional development of instructors in pre-higher education colleges